2000
DOI: 10.1128/aac.44.7.1964-1969.2000
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activities of Oral 1-O-Hexadecylpropanediol-3-Phosphoacyclovir and Acyclovir in Woodchucks with Chronic Woodchuck Hepatitis Virus Infection

Abstract: Acyclovir triphosphate is a potent inhibitor of hepatitis B virus DNA polymerase, but acyclovir treatment provides no benefit in patients with hepatitis B virus infection. This is due in part to the fact that hepatitis B virus, unlike herpes simplex virus, does not code for a viral thymidine kinase which catalyzes the initial phosphorylation of acyclovir. We synthesized 1-O-octadecyl-sn-glycero-3-phospho (3-P)-acyclovir and found that it was highly active in reducing hepatitis B virus replication in 2.2.15 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 32 publications
0
31
1
Order By: Relevance
“…Although CDV is highly active against most drug-resistant mutants, its lack of activity when given orally and the potential for producing nephrotoxicity have limited its usefulness. Hostetler and colleagues (16,17) reported that ether lipid ester analogs of PCV, GCV, and PFA had significantly increased activity against HSV and CMV as well as HBV and woodchuck hepatitis virus (15,16). These findings were subsequently extended to the synthesis of lipid conjugates for other antivirals, including CDV.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although CDV is highly active against most drug-resistant mutants, its lack of activity when given orally and the potential for producing nephrotoxicity have limited its usefulness. Hostetler and colleagues (16,17) reported that ether lipid ester analogs of PCV, GCV, and PFA had significantly increased activity against HSV and CMV as well as HBV and woodchuck hepatitis virus (15,16). These findings were subsequently extended to the synthesis of lipid conjugates for other antivirals, including CDV.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, studies with hepatitis B virus (HBV) suggest that an alkoxyalkyl-phosphate-ACV analog had significant activity in vitro and in vivo against woodchuck hepatitis virus (15,16). The hexadecyloxypropyl-phospho-ACV (HDP-P-ACV) compound also exhibited little or no toxicity (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these compounds are active orally in animal models of herpesvirus disease (16) and hepatitis (15). To obtain better oral activity with CDV, we synthesized a new series of analogs by esterification using two long-chain alkoxyalkanols, 3-hexadecyloxy-1-propanol (HDP-CDV; HDP-cCDV) and 3-octadecyloxy-1-ethanol (ODE-CDV; ODE-cCDV) (Fig.…”
mentioning
confidence: 99%
“…The monophosphate form is then converted into the active NTP (Fig. 2b) (45). Another example of a nucleoside lipid prodrug is YNK-01, an AraC analog (46).…”
Section: Liver Targetingmentioning
confidence: 99%